IMPLEMENTING A DIGITAL TECHNOLOGY-INTEGRATED ENGLISH SYLLABUS FOR ADAPTIVE AND INTERACTIVE LEARNING IN COMMUNITY LEARNING CENTERS - Rerung, Kartika Sari Tandi; Junita, Junita (Universitas Bunda Mulia, 2025)
This community service project focused on implementing a digital technology-integrated English syllabus to support adaptive and interactive learning in community learning centers run by ISCO (Indonesian Street Children Organization). The program developed ten lesson plans for Grade 7 learners, covering monthly topics from January to December. Each lesson was designed to be simple, engaging, and accessible, using a communicative and values-based approach with low-tech teaching materials that can be used in limited-resource settings although classroom implementation is planned for the next phase, the materials were reviewed by ISCO tutors who will teach them. Their feedback showed that the lesson plans are well-structured, easy to use, and suitable for community-based education. Tutors also recommended improvements—such as adding ice breakers to more sessions and expanding examples of factual statements—which were included in the final revision. This project shows that a digital-supported, value-based English syllabus can be effectively designed for low-resource, informal education settings. It supports both student learning and tutor confidence, and serves as a model for other non-formal learning environments. The approach aligns with current research on digital learning, inclusive teaching, and character education